# In the figure 2.22, M is themidpoint of QR. ∠PRQ = 90°. Prove that, PQ2 = 4PM2 – 3PR2 In ∆PRQ, PRQ = 900

PQ2 = PR2 + QR2 – – – 1

In ∆PRM, PRM = 900

PM2 = PR2 + MR2

PM2 = PR2 + 2 [ M is midpoint]

4(PM2 – PR2) = QR2 – – – 2

1 And 2 implies

PQ2 = PR2 + 4(PM2 – PR2)

PQ2 = 4PM2 – 3PR2

PROVED.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  A Peep into Pythagoras Theorem43 mins  Quiz | Pythagoras Theorem48 mins  A Peep into Pythagoras Theorem43 mins  History of Pythagoras and His Theorem37 mins  Foundation | Sum of the Series43 mins  Basics of Binomial Theorem39 mins  Fundamental Theorem of Arithmetic- 143 mins  Basic Proportionality Theorem44 mins  Basic Proportionality Theorem34 mins  Champ Quiz | Thales Theorem49 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 